2022
DOI: 10.1093/plphys/kiac372
|View full text |Cite
|
Sign up to set email alerts
|

Native architecture and acclimation of photosynthetic membranes in a fast-growing cyanobacterium

Abstract: Efficient solar energy conversion is ensured by the organization, physical association, and physiological coordination of various protein complexes in photosynthetic membranes. Here, we visualize the native architecture and interactions of photosynthetic complexes within the thylakoid membranes from a fast-growing cyanobacterium Synechococcus elongatus UTEX 2973 (Syn2973) using high-resolution atomic force microscopy (AFM). In the Syn2973 thylakoid membranes, both photosystem I (PSI)-enriched domains and cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…This situation is significantly different from that of red algae, where two PSI subcomplexes are connected to two ends of PSII array 20 , suggesting the interaction fashion of PSII with PSI is distinguished between cyanobacteria and red algae. This is likely reasonable because AFM observation for thylakoid membranes of cyanobacterium Synechococcus elongatus UTEX 2973 corroborated that PSII arrays are interspersed with PSI, which exhibits diverse interaction patterns and inhomogeneous arrangement in native thylakoid membranes 26,27 . We also identified 180 phycocyanobilin (PCB) for each PBS, and 70 chlorophylls, 4 heme molecules, 18 carotenoids and 56 lipids for each PSII dimer.…”
Section: Overall Structure Of In Situ Cyanobacterial Pbs-psii Superco...mentioning
confidence: 77%
See 1 more Smart Citation
“…This situation is significantly different from that of red algae, where two PSI subcomplexes are connected to two ends of PSII array 20 , suggesting the interaction fashion of PSII with PSI is distinguished between cyanobacteria and red algae. This is likely reasonable because AFM observation for thylakoid membranes of cyanobacterium Synechococcus elongatus UTEX 2973 corroborated that PSII arrays are interspersed with PSI, which exhibits diverse interaction patterns and inhomogeneous arrangement in native thylakoid membranes 26,27 . We also identified 180 phycocyanobilin (PCB) for each PBS, and 70 chlorophylls, 4 heme molecules, 18 carotenoids and 56 lipids for each PSII dimer.…”
Section: Overall Structure Of In Situ Cyanobacterial Pbs-psii Superco...mentioning
confidence: 77%
“…The copyright holder for this this version posted December 18, 2023. ; https://doi.org/10.1101/2023.12.17.572042 doi: bioRxiv preprint are interspersed with PSI, which exhibits diverse interaction patterns and inhomogeneous arrangement in native thylakoid membranes 26,27 . We also identified 180 phycocyanobilin (PCB) for each PBS, and 70 chlorophylls, 4 heme molecules, 18 carotenoids and 56 lipids for each PSII dimer.…”
Section: Overall Structure Of In Situ Cyanobacterial Pbs-psii Superco...mentioning
confidence: 99%
“…The RCII/PSI complex therefore appears to be artefactual, although we cannot totally exclude the possibility that the complex might reflect interactions at an early stage of PSII assembly within specialised but still ill-defined biogenesis regions of the membrane 22 . Recent work has also suggested that trimeric PSI complexes might exist in opposite orientations in the thylakoid membrane 23 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The RCII/PSI complex therefore appears to be artefactual, although we cannot totally exclude the possibility that the complex might reflect interactions at an early stage of PSII assembly within specialised but still ill-defined biogenesis regions of the membrane 22 . Recent work has also suggested that trimeric PSI complexes might exist in opposite orientations in the thylakoid membrane 23 .…”
Section: Overall Structure Of the Rcii/psi Complexmentioning
confidence: 99%